2008
DOI: 10.1021/jp077100c
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature Chemical Vapor Deposition of Aluminum and Aluminum Oxides on Alkanethiolate Self-Assembled Monolayers

Abstract: We have investigated the reaction of trimethylaluminum (TMA) with -CH 3 , -OH, and -COOH terminated self-assembled monolayers (SAMs) adsorbed on Au, using time-of-flight secondary ion mass spectrometry and X-ray photoelectron spectroscopy. TMA is a well-known atomic layer deposition precursor that is employed commercially to deposit compound semiconductors, alumina, and nitrides. We demonstrate that TMA can be employed to deposit both alumina and aluminum on SAMs at room temperature. TMA reacts with -OH and -C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 89 publications
2
30
0
Order By: Relevance
“…We have demonstrated that aluminum (and alumina) can be selectively deposited on SAMs at room temperature using the ALD precursor, trimethyl aluminum (TMA). 29 TMA reacts with -OH-and -COOH-terminated SAMs to form a surface-bound dimethyl aluminum complex, but it does not react with terminal groups that do not contain oxygen, for example, -CH 3 -terminated SAMs. If the deposition is carried out under very high vacuum (<10 -8 torr), a metallic overlayer is deposited on -OH-and -COOH-terminated SAMs with no reaction on -CH 3 -terminated SAMs.…”
Section: New Methods For the Metallization Of Organic Surfacesmentioning
confidence: 99%
“…We have demonstrated that aluminum (and alumina) can be selectively deposited on SAMs at room temperature using the ALD precursor, trimethyl aluminum (TMA). 29 TMA reacts with -OH-and -COOH-terminated SAMs to form a surface-bound dimethyl aluminum complex, but it does not react with terminal groups that do not contain oxygen, for example, -CH 3 -terminated SAMs. If the deposition is carried out under very high vacuum (<10 -8 torr), a metallic overlayer is deposited on -OH-and -COOH-terminated SAMs with no reaction on -CH 3 -terminated SAMs.…”
Section: New Methods For the Metallization Of Organic Surfacesmentioning
confidence: 99%
“…No reaction was observed with -CH 3 but reactions were observed with -OH and -COOH. In the latter cases room temperature deposition created Al oxide and Al layers under conditions of N 2 purging and UHV, respectively [79,88,89].…”
Section: Almentioning
confidence: 99%
“…Technologies besides PVD to deposit metals and other materials in Si-based microelectronics include CVD [18], atomic layer deposition (ALD) [19] and electrodeposition [20]. CVD [13] and ALD [21] have been demonstrated to produce stable contacts, but these methods are generally very slow and so are not practical.…”
Section: Electroless Depositionmentioning
confidence: 99%
“…Second, a SAM of different composition is adsorbed in the areas where the first to construct complex 2-D and 3-D structures. PVD and room temperature CVD is employed to selectively deposit Mg [12] and Al [13], respectively, on patterned -COOH/-CH 3 terminated SAMs. Compound semiconductors, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation